Amiodarone use and prolonged mechanical ventilation after cardiac surgery: a single-center analysis - Xin Li; Haitao Zhang; Yuanxi Luo; Jiqing Zhu; Dongjin Wang; Li Xu (BMC Cardiovascular Disorders)
Abstract Background Prolonged mechanical ventilation (PMV) after cardiac surgery increases the risk of complications such as pulmonary atelectasis and ventilator-associated pneumonia. This study aims to investigate the risk factors associated with delayed extubation, including the impact of cardiovascular medication. Method This retrospective, single-center study analyzed 1,976 patients who underwent open heart surgery at Nanjing Drum Tower Hospital from October 2020 to January 2023. Patients were categorized into early extubation (n = 1071) and delayed extubation (n = 905) groups. Multivariate logistic regression was employed to identify risk factors for delayed extubation. Amiodarone were indicated to be associated with delayed extubation. To further address bias, we derived a propensity score predicting the function of Amiodarone on delayed extubation, and matched 228 cases to 684 controls with similar risk profiles. Results Multivariate analysis confirmed that hypertension, stroke, amiodarone use, age, LVEF, CPB time, and DHCA were significant predictors of delayed extubation. Postoperative use of amiodarone was significantly associated with delayed extubation (OR:1.753, 95%CI: 1.287–2.395, P < 0.001). PSM analysis further confirmed that patients receiving amiodarone had longer ventilation times, prolonged hospital stays, and higher in-hospital mortality. Conclusion Postoperative use of amiodarone is a significant predictor of delayed extubation, warranting careful consideration in clinical practice. Further research is needed to clarify the causal relationship between amiodarone use and extubation outcomes.